DSM‐5 OBSESSIVE‐COMPULSIVE AND RELATED DISORDERS: CLINICAL IMPLICATIONS OF NEW CRITERIA. Issue 6 (10th March 2014) - Van Ameringen, Michael; Patterson, Beth; Simpson, William
<x xml:space="preserve">Abstract</x> For the publication of DSM‐5, obsessive‐compulsive disorder (OCD) was the subject of significant revisions to its classification and diagnostic criteria. One of these significant changes was the placement of OCD in a new category, "Obsessive‐Compulsive and Related Disorders (OCRDs), " which also includes body dysmorphic disorder (BDD), trichotillomania (hair‐pulling disorder), excoriation (skin‐picking) disorder, hoarding disorder, substance/medication‐induced OCRD, OCRD due to another medical condition, and other specified OCRDs. Changes in the diagnostic criteria and grouping of these disorders may have significant clinical implications, and will be reviewed in this article.